An isolated substorm and associated phenomena observed during the first coordinated Arase and ground-based observations - Yoshimasa, Tanaka; Takanori, Nishiyama; Akira, Kadokura; Mitsunori, Ozaki; Kazuo, Shiokawa; Shin-ichiro, Oyama; Masahito, Nose; Tsutomu, Nagatsuma; Masaki, Tsutsumi; Koji, Nishimura; Kaoru, Sato; Yoshizumi, Miyoshi; et al. (2017)
第8回極域科学シンポジウム/個別セッション：[OS] 宙空圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OS] Space and upper-atmosphere sciences Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object